Energy in buildings—Policy, materials and solutions. (30th October 2017) - Koebel, Matthias M.; Wernery, Jannis; Malfait, Wim J.
ABSTRACT: Abstract : This manuscript provides a bird's eye view on energy in buildings. We discuss how energy policy leads to building standards that affect innovation in the building sector. We review current and future materials and solutions for the building envelope (insulation and glazing), renewable energy generation and energy storage, and demonstrate how the integration of buildings into district networks mitigates problems arising from a building's, and its users', dynamic behavior. Buildings account for ∼40% of global energy demands, and the increased adoption of innovative solutions for buildings represents an enormous potential to reduce energy demands and greenhouse gas emissions. Here, we critically review the current and future materials and solutions for the construction sector. We describe how policy affects innovative businesses and the adoption of new products and solutions. We investigate how the building envelope and user behavior determine building energy demands. Compared to conventional solutions, superinsulation materials (vacuum insulation panels, silica aerogel) can achieve the same thermal performance with drastically thinner insulation. With low-emissivity coatings and appropriate filler gasses, double and triple glazing reduces thermal losses by an order of magnitude. Vacuum and aerogel glazing reduce these even further. Switchable glazing solutions maximize solar gains during wintertime and minimize illumination demands whilst avoiding overheating in summer. Upon integration of renewable energy systems, buildings become both producers and consumers of energy. Combined with the dynamic user behavior, temporal variations in energy production require thermal and electrical storage and the integration of buildings into smart grids and energy district networks. The combination of these measures can reduce the energy consumption of the building's stock by a factor of three.